"I'm Not Mopping the Floors, I'm Putting a Man on the Moon": How NASA Leaders Enhanced the Meaningfulness of Work by Changing the Meaning of Work. (June 2018) - Carton, Andrew M.
It is assumed that leaders can boost the motivation of employees by communicating the organization's ultimate aspirations, yet evidence on the effectiveness of this tactic is equivocal. On some occasions, it causes employees to view their work as more meaningful. At other times, it causes them to become dispirited. These inconsistent findings may in part be explained by a paradox: the very features that make ultimate aspirations meaningful—their breadth and timelessness—undermine the ability of employees to see how their daily responsibilities are associated with them. To understand how leaders can help employees resolve this paradox, I analyzed archival evidence to explore the actions of President John F. Kennedy when leading NASA in the 1960s. I found that Kennedy enacted four sensegiving steps, each of which helped employees see a stronger connection between their work and NASA's ultimate aspirations. When this connection was strongest, employees construed their day-to-day work not as short-term tasks ("I'm building electrical circuits") but as the pursuit of NASA's long-term objective ("I'm putting a man on the moon") and the aspiration this objective symbolized ("I'm advancing science"). My findings redirect research by conceptualizing leaders as architects who motivate employees most effectively when they provide a structural blueprint that maps the connections between employees' everyday work and the organization's ultimate aspirations.